Change of Apoptosis and Glucose Metabolism in Lung Cancer Xenografts during Cytotoxic and Anti-Angiogenic Therapy Assessed by Annexin V Based Optical Imaging and 18F-FDG-PET/CT. (13th April 2021) - Gross, Jasmin; Palmowski, Karin; Doleschel, Dennis; Rix, Anne; Gremse, Felix; Verburg, Frederic; Mottaghy, Felix M.; Kiessling, Fabian; Lederle, Wiltrud; Palmowski, Moritz
Abstract : Aim of the Study . To compare Annexin V-based optical apoptosis imaging with the assessment of the glucose metabolism using 18 F-FDG-PET/CT for monitoring the response to cytotoxic (carboplatin) and anti-angiogenic (sunitinib) therapy. Methods . For apoptosis imaging, the near-infrared probe Annexin Vivo750 was used in combination with fluorescence molecular tomography and microcomputed tomography (FMT/ µ CT). Glucose metabolism was assessed using 18 F-FDG-PET/CT. Five groups of nude mice bearing lung cancer xenografts (A549) were investigated: (i) untreated controls and two groups after (ii) cytotoxic (carboplatin) or (iii) anti-angiogenic (sunitinib) treatment for four and nine days, respectively. Imaging data were validated by immunohistochemistry. Results . In response to carboplatin treatment, an inverse relation was found between the change in glucose metabolism and apoptosis in A549 tumors. Annexin Vivo showed a continually increasing tumor accumulation, while the tumor-to-muscle ratio of 18 F-FDG continuously decreased during therapy. Immunohistochemistry revealed a significantly higher tumor apoptosis (p = 0.007 ) and a minor but not significant reduction in vessel density only at day 9 of carboplatin therapy. Interestingly, during anti-angiogenic treatment there was an early drop in the tumor-to-muscle ratio between days 0 and 4, followed by a subsequent minor decrease ( 18 F-FDG tumor-to-muscle-ratio: 1.9 ± 0.4; day 4: 1.1 ± 0.2; day 9: 1.0 ± 0.2; p = 0.021 and p = 0.001, respectively). The accumulation of Annexin Vivo continuously increased over time (Annexin Vivo: untreated: 53.7 ± 36.4 nM; day 4: 87.2 ± 53.4 nM; day 9: 115.1 ± 103.7 nM) but failed to display the very prominent early induction of tumor apoptosis that was found by histology already at day 4 (TUNEL: p = 0.0036 ) together with a decline in vessel density (CD31: p = 0.004 ), followed by no significant changes thereafter. Conclusion . Both molecular imaging approaches enable visualizing the effects of cytotoxic and anti-angiogenic therapy in A549 tumors. However, the early and strong tumor apoptosis induced by the anti-angiogenic agent sunitinib was more sensitively and reliably captured by monitoring of the glucose metabolism as compared to Annexin V-based apoptosis imaging.